I’m pretty sure the answer is C :)
Answer:
m ∠JPN = 131°
Step-by-step explanation:
m ∠JPL = m ∠MPK Vertical angles are =
7x + 19 = 11x -17 Substitution
- 4x = -36 Algebra: Solving for x
x = 9 Algebra: Solving for x
m ∠JPL = 82° Substitution x = 9 into m ∠JPL = 7x +19
m ∠JPL + m ∠LPK = 180° Definition of linear pair/supplement
angles = 180°
82° + m ∠LPK = 180° Substitution
m ∠LPK = 98° Algebra
m ∠LPK = m ∠LPN + m ∠NPK Angle addition Theorem
PN bisects ∠LPK Given
m ∠LPN = m ∠NPK Definition of angle bisector
98 ° = 2 ( m ∠LPN) Substitution
m ∠LPN = 49° Algebra
m ∠JPN = m ∠JPL + m ∠LPN Angle Addition
m ∠JPN = 82° + 49° Substitution
m ∠JPN = 131° Addition
First, notice that:
![2\tan (\frac{x}{2})=2\cdot(\pm\sqrt[]{\frac{1-cosx}{1+\cos x})}](https://tex.z-dn.net/?f=2%5Ctan%20%28%5Cfrac%7Bx%7D%7B2%7D%29%3D2%5Ccdot%28%5Cpm%5Csqrt%5B%5D%7B%5Cfrac%7B1-cosx%7D%7B1%2B%5Ccos%20x%7D%29%7D)
And in the denominator we have:
![1+\tan ^2(\frac{x}{2})=1+\frac{1-\cos x}{1+\cos x}=\frac{1+cosx+1-\cos x}{1+cosx}=\frac{2}{1+\cos x}](https://tex.z-dn.net/?f=1%2B%5Ctan%20%5E2%28%5Cfrac%7Bx%7D%7B2%7D%29%3D1%2B%5Cfrac%7B1-%5Ccos%20x%7D%7B1%2B%5Ccos%20x%7D%3D%5Cfrac%7B1%2Bcosx%2B1-%5Ccos%20x%7D%7B1%2Bcosx%7D%3D%5Cfrac%7B2%7D%7B1%2B%5Ccos%20x%7D)
then, we have on the original expression:
![\begin{gathered} \frac{2\tan(\frac{x}{2})}{1+\tan^2(\frac{x}{2})}=\frac{2\cdot\pm\sqrt[]{\frac{1-\cos x}{1+cosx}}}{\frac{2}{1+\cos x}}=\frac{2\cdot(\pm\sqrt[]{1-cosx})\cdot(1+\cos x)}{2\cdot(\sqrt[]{1+cosx})} \\ =(\sqrt[]{1-\cos x})\cdot(\sqrt[]{1+\cos x})=\sqrt[]{(1-\cos x)(1+\cos x)} \\ =\sqrt[]{1-\cos^2x}=\sqrt[]{\sin^2x}=\sin x \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20%5Cfrac%7B2%5Ctan%28%5Cfrac%7Bx%7D%7B2%7D%29%7D%7B1%2B%5Ctan%5E2%28%5Cfrac%7Bx%7D%7B2%7D%29%7D%3D%5Cfrac%7B2%5Ccdot%5Cpm%5Csqrt%5B%5D%7B%5Cfrac%7B1-%5Ccos%20x%7D%7B1%2Bcosx%7D%7D%7D%7B%5Cfrac%7B2%7D%7B1%2B%5Ccos%20x%7D%7D%3D%5Cfrac%7B2%5Ccdot%28%5Cpm%5Csqrt%5B%5D%7B1-cosx%7D%29%5Ccdot%281%2B%5Ccos%20x%29%7D%7B2%5Ccdot%28%5Csqrt%5B%5D%7B1%2Bcosx%7D%29%7D%20%5C%5C%20%3D%28%5Csqrt%5B%5D%7B1-%5Ccos%20x%7D%29%5Ccdot%28%5Csqrt%5B%5D%7B1%2B%5Ccos%20x%7D%29%3D%5Csqrt%5B%5D%7B%281-%5Ccos%20x%29%281%2B%5Ccos%20x%29%7D%20%5C%5C%20%3D%5Csqrt%5B%5D%7B1-%5Ccos%5E2x%7D%3D%5Csqrt%5B%5D%7B%5Csin%5E2x%7D%3D%5Csin%20x%20%5Cend%7Bgathered%7D)
therefore, the identity equals to sinx
Answer:
the answer is 3.
Step-by-step explanation:
mode if what numberhappens most often